Flexible, polymer-supported synthesis of sphingosine derivatives provides ceramides with enhanced biological activity - El-Dahshan, Adeeb; Al-Gharabli, Samer I.; Radetzki, Silke; Al-Tel, Taleb H.; Kumar, Pradeep; Rademann, Joerg (Bioorganic & Medicinal Chemistry, 2014)
A polymer-supported route for the synthesis of sphingosine derivatives is presented based on the C-acylation of polymeric phosphoranylidene acetates with an Fmoc-protected amino acid. The approach enables the flexible variation of the sphingosine tail through a deprotection-decarboxylation sequence followed by E-selective Wittig olefination cleavage. D-Erythro-sphingosine analogs have been synthesized by diastereoselective reduction of the keto group employing LiAlH(O-tBu)(3) as reducing agent. The effect of ceramides and keto-ceramides on the proliferation of three cancer cell lines HEP G-2, PC-12 and HL-60 was investigated and a ceramide containing an aromatic sphingosine tail was identified as being most active. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Ceramide; Lipid rafts; Lipids; Sphingosine